Cooperative Learning Klasikal dalam Pembelajaran Kitab Kuning: Studi pada Pondok Pesantren Miftahul Ulum Lumajang - Hafid, Hafid; Fawaidi, Badrun (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This study aims to evaluate the effectiveness of the Classical Cooperative Learning model in the study of Kitab Kuning at Pondok Pesantren Miftahul Ulum, Lumajang, using an input-process-output evaluation approach. The research method employed is descriptive qualitative, with data collection techniques including observation, interviews, and document analysis. The Classical Cooperative Learning model at this pesantren consists of four stages: material explanation, group learning, assessment, and team recognition. The results indicate that the Classical Cooperative Learning model is effective in enhancing students' understanding of Kitab Kuning. The material explanation stage helps students comprehend complex vocabulary and language structures. The group learning stage facilitates active interaction and cooperation among students, which improves collective understanding. Assessment through tests and quizzes comprehensively measures individual and group progress. The team recognition stage provides additional motivation for students by rewarding group achievements. The implications of this study suggest that the Classical Cooperative Learning model can be applied as an effective method for Kitab Kuning learning in other pesantren. With its structured and group cooperation-based approach, this model not only enhances academic achievement but also social skills and student motivation.